1983
DOI: 10.1111/j.1476-5381.1983.tb11057.x
|View full text |Cite
|
Sign up to set email alerts
|

Substance P modulates the sensitivity of the nicotinic receptor in amphibian cholinergic transmission

Abstract: 1 The effect of substance P on the sensitivity of nicotinic acetylcholine (ACh) receptors of bullfrog sympathetic ganglion cells and frog skeletal muscle endplate was examined electrophysiologically. 2 The amplitude of ACh-induced postsynaptic potential (ACh potential) and current (ACh current) were reversibly and dose-dependently reduced by substance P at low concentrations (0.42-42 AM).3 The mean amplitude of the miniature endplate potential (m.e.p.p.) was also reduced by substance P (4.2 pM).4 Substance P (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
24
1

Year Published

1984
1984
2000
2000

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(27 citation statements)
references
References 31 publications
2
24
1
Order By: Relevance
“…These results are different from a recent report on bullfrog sympathetic ganglia in which, after a 2-to 3-min bath application of substance P, the peptide apparently decreased the peak current response to iontophoretically applied AcCho by =40% with no effect on the time course of current decay (14). The discrepancy between the results is difficult to resolve given the different preparations studied.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…These results are different from a recent report on bullfrog sympathetic ganglia in which, after a 2-to 3-min bath application of substance P, the peptide apparently decreased the peak current response to iontophoretically applied AcCho by =40% with no effect on the time course of current decay (14). The discrepancy between the results is difficult to resolve given the different preparations studied.…”
Section: Discussioncontrasting
confidence: 99%
“…ref. 14), although several studies have demonstrated a direct depolarization of mammalian and amphibian sympathetic neurons by the peptide (15)(16)(17)(18).…”
mentioning
confidence: 99%
“…This inhibitory action of SP was markedly enhanced by pre-exposure to SP for 10min before nicotine (Figure 4). Inhibitory effects of SP on the nicotinic responses have been described for a number of different preparations including cat spinal Renshaw cells (Belcher & Ryall, 1977;Krnjevic & Lekic, 1977), bovine isolated chromaffin cells (Livett et al, 1979;Role et al, 1981;Boksa & Livett, 1984b), frog sympathetic ganglia and skeletal muscle endplates (Akasu et al, 1983), (Stallcup & Patrick, 1980;Simasko et al, 1985;Boyd & Leeman, 1987), BC3H1 cells (Simasko et al, 1985) and rat adrenal gland slices (Nieber & Oehme, 1987). This action which is Ca2"-dependent and specific to nicotinic receptor function (Boksa & Livett, 1984b;Role et al, 1981) has an IC50 for SP of about 10-6M (Boksa & Livett, 1984b;Simasko et al, 1987).…”
Section: Discussionmentioning
confidence: 99%
“…None of these substances alter the equilibrium potential [7,8,9,17,43]. The time constant of the falling phase of the end-plate current is not decreased by catecholamines [43] and polypeptides [8,9], suggesting that these transmitters change the conductance of the single channel. One interesting characteristic of the nicotinic ACh-receptor is desensitization.…”
Section: A) Experimental Evidencementioning
confidence: 99%
“…AKASU et al [9] reported that substance-P decreased the sensitivity of the nicotinic ACh-receptor in bullfrog sympathetic ganglion cells and at frog skeletal muscle endplates. Analyses of the effects of substance-P on the dose-response relationship for the ACh-current indicated that the action of substance-P is similar to that of LH-RH [8].…”
Section: A) Experimental Evidencementioning
confidence: 99%